(untitled) (Colombia Medica, 2019)
Aim: To characterize the Tpeak-Tend, the Tpeak-Tend dispersion and Tpeak-Tend/QT in children and its relationship with clinical variables. Methods: Cross-sectional study in 126 children between 9 and 12 years of the Camilo Cienfuegos School in Santa Clara, Cuba. Clinical and anthropometric variables were obtained to determine their relationship with electrocardiographic parameters: Tpeak-Tend V5, Tpeak-Tend dispersion and Tpeak-Tend/QT ratio V5. In addition, laboratory tests were conducted. Results: Age and systolic blood pressure are associated with an increased probability of having values ​​of Tpeak-Tend/QT V5 ≥75 percentile for both sexes (OR: 1.72, CI 95%: 1.02-2.91; p= 0.043), (OR: 1.08, CI 95%: 1.01-1.16; p= 0.017) respectively. The body mass index and systolic blood pressure are linearly and significantly correlated with the Tpeak-Tend/QT V5 (r= 0.224; p= 0.012) and (r= 0.220; p= 0.014) respectively. Conclusions: The age of the patients and the systolic blood pressure figures are factors that increase the probability of having values ​​of the Tpeak-Tend/QT V5 ≥75 percentile. There was a significant linear correlation between the Tpeak-Tend/QT V5 with the body mass index and the systolic blood pressure.